Xanthine Oxidase Inhibitory Activity of Ethanolic Extract of Ficus Carica Fruit - Zoobia Irum, Amer Hassan Siddiqui, Fariha Ahmad Khan, Fouzia Perveen, Asia Firdous, Neelofer Yousaf, (Pakistan Journal of Medical & Health Sciences, 2023)
Hyperuricemia is a purine metabolism disorder characterised by an excess of uric acid in the blood and considered as a risk factor for gout, coronary heart disease, hypertension, diabetes, and a variety of other illnesses. Xanthine oxidase inhibitors have key role in management of hyperuricemia and related disorders but multiple adverse effects associated with these agents have minimized their chronic use. Ficus carica fruit has been widely used around world as a therapeutic agent for several disorders. In traditional medicine it has been used to treat gouty arthritis but the effect has not been scientifically established so far. Objective: This study was conducted to assess the in vitro xanthine oxidase inhibition of Ficus carica fruit extract. Method: The ethanolic extract of Ficus carica fruit was evaluated in vitro at five different doses for its xanthine oxidase inhibition. Xanthine oxidase inhibitory activity was measured spectrophotometrically and inhibitory concentration IC 50 was calculated. The dose dependant inhibition of Ficus carica fruit was compared with inhibition of standard drug allopurinol. Results: Ficus carica fruit extract was found to possess xanthine oxidase inhibition with IC50 27.5 µg/ml in comparison to the allopurinol with IC50 11.0 µg/ml.Thus the agent can be used as alternative to standard drug allopurinol for treatment of hyperuricemia and related disorders. Conclusion: The study showed that Ficus carica fruit has potential to inhibit the xanthine oxidase so can be used as natural source to treat gout and many other xanthine oxidase related medical disorders. Keywords: Ficus carica Extract (FCE), Xanthine Oxidase (XO), Xanthine Oxidase Inhibition (XOI), Hyperuricemeia (HU).